Foot and mouth disease and F.M.D. outbreak in Evros Prefecture in 2000 - DADOUSIS (Κ. ΔΑΔΟΥΣΗΣ), K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Foot and mouth disease (FMD) is an extremely, highly contagious, acute disease of all cloven-footed animal species. From 1994 to 2000 three FMD outbreaks occurred in Evros Prefecture and caused serious economical losses to the livestock of Evros. Particularly, in 1994 22 catde and 375 small ruminants were destroyed. In 1996, 6.250 catde, 24.261 small ruminants and 647 pigs were destroyed. Finally, in 2000, 5.383 catde, 4.405 small ruminants and 359 pigs were destroyed. All outbreaks, which occurred in Evros in 1994, in 1996 and 2000, were controlled by stamping-out of infected herds and flocks and pre-emptive culling on neighbouring and contact farms. FMD virus type Ο was isolated in 1994 and in 1996 and virus type ASIAl5 in 2000. In 2000 outbreak virus predominantly affected the catde population. All infected cattle showed clinical signs and high susceptibility in this strain of type ASIAj. Sheep, goats and pigs showed registans against this type ASIAj virus and clinical signs were found in only two flocks of sheep and in one of goats and pigs. In 2000, occurred the first and unique case of ASIAj in pings. Control measures lasted 5 months. In this review, all the symptomatology of FMD and the control measures, based on the experience of all these years, are given. Also, statistics and photo images are included.